Evaluation of antibiotic susceptibility of Burkholderia pseudomallei isolated from melioidosis patients in northern Vietnam - Nguyen Phuong Anh; Vu Thi Ngoc Anh; Tran Thi Le Quyen; Bui Nguyen Hai Linh; Trinh Thanh Trung (Vietnam Journal of Science, Technology and Engineering)
Melioidosis is a potentially fatal infectious disease caused by the gram- negative bacterium Burkholderia pseudomallei. This disease is prevalent in northern Australia and Southeast Asia, including Vietnam. Therapeutic options are limited to a selected group of six antibiotics: amoxicillin/clavulanic acid, ceftazidime, doxycycline, imipenem, meropenem, and trimethoprim/sulfamethoxazole. Although recent efforts have been made to detect cases of melioidosis, the antibiotic resistance of B. pseudomallei in Vietnam has been poorly investigated. In this study, the susceptibility of 53 B. pseudomallei strains isolated from melioidosis patients in northern Vietnam was determined using the broth microdilution assay and the E-test method. All strains (100%) were susceptible to doxycycline (minimum inhibitory concentration - MIC range: 0.5-4 µg/ml), imipenem (MIC range: 0.25-1 µg/ml), meropenem (MIC range: 0.5-4 µg/ml), and trimethoprim/sulfamethoxazole (MIC range: 0.032/0.608-0.75/14.25 µg/ml). One strain (1.9%) exhibited intermediate resistance to ceftazidime, and two strains (3.8%) demonstrated intermediate resistance to amoxicillin/clavulanic acid. Our findings indicate that the majority of clinical B. pseudomallei strains isolated from melioidosis patients in northern Vietnam remain susceptible to the six antibiotics currently recommended for the treatment of this disease.